RELATIONSHIP BETWEEN CADRE PARTICIPATION WITH POSYANDU ACTIVITIES IN DALIG RAYA VILLAGE SIMALUNGUN DISTRICT - Yunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The problem in this study is the relationship between cadre participation in posyandu activities in Dalig Raya Village, Raya District, Simalungun Regency. This study aims to determine the relationship between cadre participation in posyandu activities in Dalig Raya Village, Raya District, Simalungun Regency. This type of research is an analytic survey research with a cross sectional approach. The population in this study were all posyandu cadres in Dalig Raya Village, Raya District, Simalungun Regency with a total of 20 cadres. The samples taken were 19 people obtained using a random sampling technique using the Krejcie and Morgan tables. The instruments used in this study were: 1) questionnaire and 2) Observation sheets for the average coverage of D/S. The data obtained in the study were processed using the Chi Square statistical test with a 0.05. The results showed that the p values ​​of the several factors studied were as follows: 1) Knowledge of cadres about posyandu (p value -0.037); 2) The length of time the cadre has worked (p value=0.272); 3) Working hours of cadres (p value-0.249); 4) Provision of incentives (p value = 0.037), 5) Number of cadres (p value 0.530); 6) Availability of tools and materials (p value-0.574); 7) Selection (p value 0.177); 8) Development of cadres (p value=0.530); 9) Frequency of cadre meetings (p value 0.035). The results of the research and discussion concluded that there was a significant relationship between knowledge, incentives and meetings with the participation of cadres in posyandu activities in Dalig Raya Village, Simalungun Regency.